THE POTENTIAL ENVIRONMENTAL SERVICES IN THE IMPLEMENTATION OF GREEN INFRASTRUCTURE IN DEPOK AND ITS ECOREGION - Pratama, Aditya
Fulfilling the proportion of Green Open Space (RTH) of 30% of urban areas is a challenge for the Government of Depok because of the high possibility of changes in green land cover due to an increase in population in the area. Fulfillment of the proportion of green open space not only fulfills the proportion of quantity, but also has an attachment to fulfilling the city's ecological functions in order to create a comfortable life for the community. The high price of land in urban areas has added to the difficulties for the Government of Depok in providing green open space in its area. Therefore, it is necessary to cooperate in providing green open space in Depok with its ecoregion area. The determination of the ecoregion area is carried out by determining the ecological boundaries of Depok based on the watershed area (DAS) through which it passes. The results of determining the ecological boundaries of Depok are Bogor and Bogor Regency. The purpose of this research is to look at the potential for environmental services in the implementation of green infrastructure in Depok City, Bogor City, and Bogor Regency. The potential for environmental services can be seen from the ability of green infrastructure to produce oxygen and absorb carbon dioxide (CO2) emissions. In addition, this study also looks at the comparison of the quantity of green open space between before and after the implementation of green infrastructure and the Indonesian Blue Green Index (IHBI) method. The quantity of green open space is calculated based on the standard green open space needs based on the area and the standard green open space needs based on the number of inhabitants per capita. The analysis techniques used in the study are adjusted based on their respective objectives. The identification of existing green open spaces (RTH) utilizes spatial analysis combined with the calculation method of IHBI. The identification of RTH needs based on the area, population, and oxygen requirements is carried out according to the prevailing regulations in Indonesia. Meanwhile, the identification of RTH needs based on CO2 emissions is conducted using the method developed by the Intergovernmental Panel on Climate Change (IPCC) in 2006. The identification of potential green infrastructure development is done through content analysis of literature studies and regulations, as well as assessing the compatibility of regionaliv characteristics with green infrastructure typology. The identification of potential environmental benefits and services resulting from the implementation of green infrastructure is conducted through descriptive quantitative analysis, comparing the quantity and quality of green open space before and after the development of green infrastructure in each region. The results of the study show that there is an increase in the quantity of green open space after the implementation of IHBI and potential green infrastructure in each district/city. Based on the implementation of IHBI, each region can fulfill the quantity of green open space based on its area with details of Depok as much as 34% green open space from the total area, Bogor as much as 43% green open space from the area area, and Bogor Regency as much as 58% from the total area. Based on the implementation of green infrastructure, Depok and Bogor Regency have succeeded in fulfilling the need for green open space based on their area of 36% and 76% of the total area, respectively. Meanwhile, Bogor has not been able to fulfill this with the proportion of green open space of 24% of the total area. Based on the absorption of CO2 emissions after the implementation of green infrastructure, only Bogor Regency can fulfill the absorption of CO2 emissions by 2042. Depok can only fulfill the absorption of CO2 emissions until 2032. Meanwhile, Bogor cannot fulfill the absorption of CO2 emissions in 2022. There are 2,332. 210 tons of CO2/year in 2042 which cannot be absorbed by potential green infrastructure in Depok. Meanwhile, there are 6,119,135 tons of CO2/year in Bogor which cannot be absorbed in 2042. Based on the calculation of the economic value of environmental services, Bogor Regency provides potential environmental services to Depok and Bogor in the amount of Rp. 579.607.985.392. This indicates that in the ecoregion of Depok, Depok and Bogor act as benefit recipient areas and Bogor Regency acts as beneficiary areas.